Dynamics of the Leslie Type Predator-Prey Model with Effect of Fear and Delay in the Prey Population - Umapriya, D.; Kalpana, V.; Ramya, M. A.; Karthiga, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
We present the dynamics of the predator-prey model of Leslie type by introducing fear and gestation delay in the prey population to get a more realistic model. It is assumed that the predator consumes prey in the form of Beddington DeAngelis functional response. For all positive equilibrium points, the existence and local stability analysis is discussed. The condition for the local stability of coexisting equilibrium point for both delayed and non-delayed model is provided by using the Routh-Hurwitz criterion. The global stability property of the coexisting equilibrium point is analyzed with the help of constructing a suitable Lyapunov function. Also, the model shows bifurcation behavior, particularly Hopf-bifurcation at coexisting equilibrium point for both delayed and non-delayed model are proven analytically. Also, the analytical results are verified numerically in each section.